Translating SSF Guidelines Into Practice With the Small-Scale Fisheries Academy - Nauen, Cornelia E.; Arraes Treffner, Maria Fernanda (Frontiers in Marine Science, 2021)
The Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries in the Context of Food Security and Poverty Eradication (SSF Guidelines) have been adopted by FAO’s Committee of Fisheries (COFI) in 2014. In this short research report, we present action research with self-selected men and women in small-scale fisheries in Senegal, a country with a large and dynamic SSF, which suffers, however, from diminishing profitability as a result of multiple pressures. We report ongoing work on the principles and approaches of the Small-Scale Fisheries Academy as a way to support the implementation of these Guidelines. The first phase of developing the SSF Academy focuses on testing learning methods aimed at developing critical thinking, planning and action. Respectful dialogue in the secure space of the Academy made academy learners, particularly women and younger participants, gradually more confident, articulate and active. They started harvesting the results of enacted planning. We cautiously argue that it would be useful to expand these tests combining dialogue, the art of hosting communication and visual thinking to different places in Senegal and elsewhere. They provide an opportunity to address sensitive social issues like gender equity and intra-household violence and open perspectives on other societal challenges that hamper the implementation of the Guidelines. Despite the difficult conditions of the pandemic and given the rather limited work during the pilot phase before, the Academy’s participatory and inclusive learning and empowerment approach had an impact on the individual learners and the group and thus contributed to the implementation of the SSF Guidelines.